Amphotericin B Delivery From Bone Cement Increases With Porosity but Strength Decreases - Kweon, Chris (Springer-Verlag, 2011)
BACKGROUND: Amphotericin B is a highly hydrophobic antifungal used for orthopaedic infections. There is disagreement about whether amphotericin B is released when it is loaded in polymethylmethacrylate (PMMA). It is unknown how much a poragen will increase amphotericin B release or decrease the compressive strength of the PMMA. QUESTIONS/PURPOSES: We therefore measured amphotericin B release and the compressive strength of amphotericin B loaded bone cement with and without adding high-dose poragen. METHODS: Antifungal-loaded bone cement was formulated with Simplex P cement and 200 mg amphotericin B with and without 10 g cefazolin (poragen) per batch. Twenty standardized test cylinders were eluted in deionized water for each formulation. Cumulative amphotericin B mass and compressive strength were measured. Data were analyzed using repeated-measures analysis of variance. RESULTS: Antifungal-loaded bone cement (ALBC) with 10 g poragen delivered more amphotericin B than ALBC containing amphotericin B alone by Day 15, 12.76 μg/cylinder (0.5%) versus 1.74 μg/cylinder (0.04%), respectively. With amphotericin B alone, compressive strength was unchanged and compressive strength did not decrease during elution. Adding 10 g poragen to ALBC with 200 mg amphotericin B decreased the compressive strength and compressive strength decreased further during elution, 80, 61, and 46 MPa at 0, 1, and 30 days, respectively. CONCLUSIONS: Amphotericin B is released in very small amounts from antifungal-loaded bone cement. Release can be increased by adding high-dose poragen, but compressive strength decreases sufficiently to limit its use for implant fixation.